APLIKASI SISTEM INFORMASI PENJADWALAN LABORATORIUM (STUDI KASUS LABORATORIUM TRPL) - Olipio Sayudias; Linda Fujiyanti; Muhammad Setya Pratama (Politeknik Manufaktur Negeri Bangka Belitung, 2022)
The laboratory scheduling system in an educational institution is a very crucial thing to pay attention to. The practicum scheduling process at the Software Engineering Technology Laboratory (TRPL) of the Bangka Belitung State Manufacturing Polytechnic is carried out every semester and is a complicated thing to do manually. This study discusses the design of a laboratory scheduling information system application which is a solution to this problem. In designing this application using the waterfall method (waterfall) development model that emphasizes sequential and systematic phases. In addition, this system also applies the concept of genetic algorithms to assist in scheduling problems that are not yet computerized and the best solution can be found using genetic operators (selection, crossover, and mutation).